Analyzing sources to sedimentary organic carbon in the Gulf of Urabá, southern Caribbean, using carbon stable isotopes (2017)
Carbon stable isotopes analysis serve reconstruction of the origin of organic matter (OM) deposited onto sediments. They also allow tracing vegetation change at different time scales. This study weighs the contribution of both marine and terrestrial sources to sedimentary organic carbon (OC) from a southwestern Caribbean Gulf partly surrounded by large Musa acuminata (banana) croplands. The δ13C values in three sediment cores from the gulf have slightly decreased over 1000 yrs BP, indicating enhanced terrestrial input of detrital carbon owing to river discharge. A two-end mixing model fed with these δ13C values showed that averaged terrestrial contribution of OC to sediment was 52.0% at prodelta, 76.4% at delta front, and 64.2% at Colombia Bay. This agrees well with sediment dynamics. The main source of sedimentary OC within the gulf was terrestrial instead of marine. In fact, a distorted trend in δ13C values for one of the coring sites could be the result of banana crop expansion through the 20th century.